Utilization of Local Food as a Business Opportunity in Karangjatianyar Village Wonorejo Pasuruan - Miftahillah, Miftahillah; M. Mujib Utsmani; Faizatul Ilmiah (Tinta Emas Institute, 2024)
Utilization of local food in the economic crisis is a concept in the economic field that prioritizes human resources who have knowledge and creative ideas as a strategy to advance the community's economy. There are problems in Karangjatianyar Village residents such as unemployment, one of which is due to layoffs (Termination of Employment), the work program chosen is the utilization of local food as a new business opportunity in the economic crisis, namely increasing economic efforts by utilizing sweet corn processed into JaSuKe, utilizing Cassava plants so as to increase economic efforts by making Cassava chips, home businesses utilizing spicy dried noodles, tomato cultivation to improve the economy in the economic crisis. This work program involves cooperation between the village head, household heads, Cassava chip business owners, noodle home business owners, and tomato plant cultivation owners as well as local residents. With the efforts made in Karangjatianyar Village, it is hoped that it can continue to be developed by local residents to help improve the economy.